Pemberdayaan Masyarakat Pantai melalui Pelatihan Pengemasan Produk Destinasi Wisata dalam Perspektif Komunikasi Visual di Desa Kertayasa Kecamatan Cijulang Kabupaten Pangandaran - Yanti Setianti; Hanny Hafiar; Priyo Subekti (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
Community empowerment is a government program that is currently being promoted to create a creative society by recognizing the potential and existing problems surrounding the environment by exploiting local potential. One of the community empowerment efforts that is conducted by the PKM team of Public Relations Program of Fikom Unpad is through the training for community empowerment through the introduction of visual communication to design products to be more inviting and attract attention. The participants in this training consisted of youth leaders, community leaders, and village officials in terms of understanding about community empowerment through creative potential based on local creative training. Objects of activities of these institutions and figures were chosen because they are an important part of formal human resource management that exists in every village government as an element of supporting development activities in the real sector. The implementation method starts from the Preparation, Implementation and Evaluation Stage. Implementation using lecture method discussion.